Sistem Pendukung Keputusan Pemilihan Bibit Udang Vannamie Menggunakan Metode AHP (Studi Kasus : Fandi Vaname) - Muhammad Choirul Ikhwan; Umi Chotijah (Jurnal Teknika, 2022)
Fandi Vaname is a place for buying and selling vanamie shrimp seeds located in one of the villages in Glagah sub-district. The high demand for seeds by vannamie shrimp farmers makes it difficult for the buying and selling parties to determine the criteria for the best shrimp seeds. In determining the criteria for the best shrimp seeds, several methods are needed, one method that can be used is a decision support system using the AHP (Analytical Hierarchy Process) method. This method uses selection on existing criteria and determines a suitable solution to the alternative choices. Based on the results obtained by calculating the AHP method in this system, the results of the ranking of the criteria for the best alternative seeds are first occupied by the Vannamie PL 11 type, then in second place, namely the Vannamie PL 9 type and finally the Vannamie PL 14 type, and the results of the system are appropriate. The existence of a decision support system using the AHP (Analytical Hierarchy Process) method on Fandi Vaname can help the buying and selling party in determining the criteria for the best shrimp seeds.